Corporate social responsibility "glocalisation": Evidence from the international construction business. (31st July 2019) - Ye, Meng; Lu, Weisheng; Flanagan, Roger; Chau, Kwong Wing
Abstract: This paper aims (a) to enrich the corporate social responsibility (CSR) globalisation–localisation dyad (called "glocalisation") by positioning it amid relevant theoretical discourses and (b) to map out CSR glocalisation patterns by focusing on international construction as a revealing business sector. It does so by triangulating field studies with content analyses of 68 international construction companies' (ICCs) CSR reports over 7 years (2011–2017) assisted by a text mining approach. By examining how categories of CSR issue are valued in different host countries, the research positions CSR glocalisation in a four‐quadrant grid model to illustrate their relationships. It is found that ICCs adopt glocalisation to strike a balance between CSR globalisation/standardisation and localisation/contextualisation to enhance the consistency and efficiency of their CSR strategies while maintaining responsiveness to the local environment. Demystification of the concept of CSR glocalisation will encourage further theoretical debate and practical applications of CSR and sustainable development in the international construction business.